Health and Family Communication: Exploring Concept and Issues - Eko Hero; Dini Sundari (UIR Press, 2020)
The phenomenon of early age marriage has occurred in many places over the world including in Indonesia. What is more, the maternal mortality rate and other risks of health reproductive had been also increased. Numerous of argumentations that the pregnancy at a young age will create a higher chance of females having a bunch of children and a higher risk of death of the mother and child. Likewise, analyzing important issues regarding marriage at a young age is very important to provide a deep scientific understanding. Through a qualitative approach, this study aims to explore the conceptual issues about health communication which involves reproductive health, negotiation, early-age marriage, and family communication. Health communication is the role of communication to disseminate health information in the form of communication with patients, family, and community. Reproductive health is about all matters related to a reproductive system including its functions and processes. Negotiation concerns the interactive process done to reach an agreement that involves two or more people who have different perspectives and willing to reach the same resolution together. The early-age marriage is a formal or non-formal marriage done below 18 years of age. Family communication is a communication activity done in a family in which a process of exchanging meaning includes delivering emotion among its members.